PENANAMAN BERSAMA 2000 MANGROVE SEJATI OLEH MASYARAKAT DUSUN V PEMATANG KUALA DAN TIM PENGABDIAN MASYARAKAT UISU - Pandu Prabowo W.; Rahmad Setia Budi; Sularno Sularno; Edi Azwar; Jalilah Ilmiha; Maulidya Rahmah; Eka Hidayat Nst; Zikir Amin Nazara (Universitas Islam Sumatear Utara, 2023)
The village that is in the spotlight this time is Pematang Kuala Village, where this village has a livelihood mostly as farmers, fishermen and laborers. Serdang Bedagai Regency has geographical conditions in the form of lowlands where it is supported by fertile soil conditions and has most of the people whose livelihoods are farmers and fishermen. Hamlet 5 Pematang Kuala Village is the main target for Village development this time because Hamlet 5 Pematang Kuala Village has become a Partner Village of the Islamic University of North Sumatra, there have been village development activities carried out by UISU students in the form of PHP2D activities which have already completed the implementation process. Therefore it is necessary to have activities to improve the welfare of the people who are dominated by fishing communities. The East Coast of Sumatra Island has a fairly long and wide span, especially in the Serdang Bedagai area which is the longest and widest coastal area. On this occasion, we made observations of the coastal area in the village of Pematang Kuala, where this beach borders the villages of Bogak Besar and Bagan Kuala. The results of our observations in the village of Pematang Kuala are, where the physical condition of the road to the beach is bad, even though this beach has a high potential to be developed into ecotourism. In the coastal area, around 20,000 mangrove plants have been planted with an area of about 54 km2 since 2014 by the local community. The types of mangroves found in this area are Rhizopora sp and Avicennia species. Mangrove planting in this area still has a distance of about 1.5 m between one tree and another, and not all areas are planted with mangrove trees, in this area there are also no seawater breakwaters that can reduce abrasion and erosion. A pheasant or low-threshold breakwater is a coastal protection technology intended as a solution to the problem of coastal erosion and abrasion caused by tides and sea waves. The breakwater is used to control abrasion which can erode the coastline and also to calm the waves in the harbor so that ships can dock more easily and quickly in the port. In other words, briefly it can be concluded that the abrasion conditions. which were quite severe over the past 5 years resulted in the loss of the coastlin and turned into soft, difficult-to-compave mud and eroded the mangrove area. leading to further reductions in marine catches. This is a big problem that must be taken seriously. Pematang Kuala Village, which is also a UISU partner village requires the Islamic University of North Sumatra to collaborate in solving this problem. The PKM team from UISU is expected to be able to solve this critical problem by making wave-breaking bamboo pheasants and planting true mangroves.